PENGARUH INDEKS MASSA TUBUH (IMT) DAN AKTIVITAS FISIK TERHADAP KEJADIAN DISMENORE PADA REMAJA PUTRI DI KOTA KUPANG - Kadek Dwi Ariesthi (CHMK HEALTH JOURNAL, 2020)
Dysmenorrhea is a medical condition that occurs during menstruation / menstruation that can interfere with activities and require treatment that is characterized by pain or pain in the abdomen or pelvis. Dysmenorrhoea occurs in 30-75% of women and requires treatment. In Indonesia it is estimated that around 55% of productive women experience dysmenorrhea. As many as 15% of them reported that their activities were limited due to dysmenorrhea. The cause of dysmenorrhea is still not clearly known because of the many causes of factors such as: psychiatric, individual, obstruction in the cervical canal, female reproductive organs, endocrine, allergic, and nutritional intake. This study aims to analyze the effect of body mass index (BMI) and physical activity on the incidence of dysmenorrhea in young girls in Kupang City. This research is a descriptive study with cross sectional method. This research was conducted from January to February 2020 .. Data were collected with the help of a questionnaire. The number of samples in this study were 144 people. The results obtained were body mass index and physical activity affecting the incidence of dysmenorrhea in young women.